Предмет: Математика, автор: nadya7054

4 задание плизззз, срочно ​

Приложения:

Ответы

Автор ответа: yakfedor
0

Ответ:

\frac{2}{3} (3a-\frac{1}{2} ) - \frac{1}{2} (\frac{2}{3} b-1) = \frac{2*3*a}{3} -\frac{2*1}{3*2} -\frac{2*b}{2*3} +\frac{1}{2} =2a-\frac{1}{3} -\frac{1}{3} b+\frac{1}{2}=2a-\frac{1}{3} b+\frac{1}{6}

2*\frac{1}{3} -\frac{1}{3} *1+\frac{1}{6}=\frac{1}{3} +\frac{1}{6}=\frac{2}{6}+\frac{1}{6}=\frac{3}{6}=\frac{1}{2}

Похожие вопросы
Предмет: Геометрия, автор: viktor13456756
Предмет: Геометрия, автор: maks265782992